Scalable manufacturing of boron nitride nanotubes and their assemblies: a review. (1st December 2016) - Kim, Keun Su; Kim, Myung Jong; Park, Cheol; Fay, Catharine C; Chu, Sang-Hyon; Kingston, Christopher T; Simard, Benoit
Abstract: Boron nitride nanotubes (BNNTs) are wide bandgap semiconducting materials with a quasiparticle energy gap larger than 6.0 eV. Since their first synthesis in 1995, there have been considerable attempts to develop novel BNNT-based applications in semiconductor science and technology. Inspired by carbon nanotube synthesis methods, many BNNT synthesis methods have been developed so far; however, it has been very challenging to produce BNNTs at a large scale with the structural quality high enough for exploring practical applications. Very recently there has been significant progress in the scalable manufacturing of high-quality BNNTs. In this article, we will review those particular breakthroughs and discuss their impact on semiconductor industries. Freestanding BNNT assemblies such as transparent thin films, yarns or buckypapers are highly advantageous in the development of novel BNNT-based semiconductor devices. The latest achievements in their manufacturing processes will be also presented along with their potential applications.